PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING (Studi Kasus Di Dinas Pertanian Tanaman Pangan, Perkebunan Dan Kehutanan Kabupaten Karanganyar ) - ., Mulyanto; Widayati, Dyah (-)
This study aims to determine the influence of leadership, and work motivation on employee performance (patent studies Karanganyar). A hypothesis has been formulated is no significant influence on the performance leadership, motivation for performance, there is significant relationship between job satisfaction on performance. This study is a survey with 65 people jumlah sampel. The method is simple random sample collection sampling. Data used are primary data collected through questionnaires, which were distributed to the respondents. The data was obtained was tested with test validity, reliability test, regression test, t test, F test, test R2 and test the classic assumption The first regression equation: Y1 = 7,104 + 0,718 X1 + 0,737X2 – 0,614X3 + є (0,283) (0,000)** (0,001)** (0,006)** The second regression equation: Y2 = 85,128 + 2,118, X1 – 2,731 X2 - 2,589 X3 - 0,036X1M + 0,088 X2Mє (0,072) (0,061) (0,097) (0,034)** (0,217) (0,035)** From the results of the first regression equation shows that leadership has a significant positive effect on performance. Work motivation significant effect on performance. From the results of the regression equation both by moderating show that leadership, no significant effect on performance, motivation was not significant negative effect on performance, satisfaction and a significant negative effect on performance. While no significant effect of leadership satisfaction and motivation of a significant and positive influence satisfaction. The test results showed the total R2 model of this equation, the independent variable (leadership, work motivation and job satisfaction) was able to explain the dependent variable (employees performance) by 48% and the remaining 52% be explained by other variables outside of this research. Key words: leadership, work motivation, job satisfaction, employee performance.